GAMBARAN KADAR VITAMIN D PADA WANITA USIA SUBUR DI KOTA JAMBI; UPAYA AWAL PENGEMBANGAN MODEL KEBIJAKAN KESEHATAN REPRODUKSI - Herlambang Herlambang; Nyimas Natasha Ayu Safira; Amelia Dwi Fitri; Anggelia Puspasari (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2021)
ABSTRACT Deficiency and insufficiency of Vitamin D associated with reproductive associated illness in women. Previous studies reported increasing prevalence of preeclampsia, premature labor, intrauterine growth restriction and infertility in women who have deficiency and insufficiency of Vitamin D. Vitamin D plasma measurement does not perform as routine test in Indonesia, including Jambi province. Although Indonesia is tropical country that have glimpse of sunshine all year around but epidemiology study reported high prevalence of Vitamin D deficiency and insufficiency. Furthermore, we conduct Vitamin D screening in women in reproductive age as early step for develop policy associated with reproductive health. This program recruited 24 reproductive age women that getting explanation about objective and procedure will be performed. Demographic data and blood vein sample for Vitamin D measurement was taken. The author collaborated with Mitra Hospital and PRODIA laboratories for this program. Result of this screening showed all the participants have deficient and insufficient of Vitamin D plasma level, no one has normal Vitamin D plasma level. According to that result we suggested screening Vitamin D performed as routine screening for women in reproductive age and assessment of this caused of this phenomenon. Keyword: Vitamin D, Reproductive age women, reproductive health. ABSTRAK Kadar Vitamin D dibawah normal dikaitkan dengan gangguan kesehatan reproduksi pada wanita usia subur (WUS). Studi terdahulu menunjukkan peningkatan prevalensi preeklampsia, kelahiran prematur, pertumbuhan janin terhambat dan infertilitas pada WUS dengan insufisiensi dan defisiensi Vitamin D. Kadar Vitamin D bukan merupakan skrining rutin yang dikerjakan dilayanan kesehatan di Indonesia termasuk di Kota Jambi. Studi epidemiologi terdahulu menunjukkan meskipun Indonesia merupakan negara dengan sinar matahari sepanjang tahun, akan tetapi prevalensi defisiensi Vitamin masih tinggi. Sehingga pengabdian ini melakukan pemeriksaan kadar Vitamin D pada WUS sebagai upaya awal pengembangan model kebijakan kesehatan reproduksi. Sebanyak 24 orang WUS yang telah mendapatkan penjelasan tentang rangkaian kegiatan pengabdian setuju untuk mengikuti pengabdian ini. Data demografi dasar dan sampel darah vena untuk pemeriksaan kadar Vitamin D diambil pada kegiatan ini. Tim bekerjasama dengan RS Mitra dan laboratorium PRODIA terkait dengan pelaksanaan kegiatan dimasa COVID-19. Hasil pemeriksaan Vitamin D didapatkan kadar Vitamin D plasma dalam kategori insufisien dan defisien, tidak ada yang memiliki kadar plasma Vitamin D normal. Terkait hasil tersebut ,hendaknya skrining Vitamin D dapat dijadikan program pelayanan kesehatan rutin dan dilaksanakan kajian menyeluruh menegnai hal tersebut untuk mendukung intervensi lebih lanjut. Katakunci: Vitamin D, Wanita Usia Subur, Kesehatan Reproduksi